2021
DOI: 10.1097/shk.0000000000001764
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock and Resuscitation Causes Glycocalyx Shedding and Endothelial Oxidative Stress Preferentially in the Lung and Intestinal Vasculature

Abstract: Hemorrhagic shock has recently been shown to cause shedding of a carbohydrate surface layer of endothelial cells known as the glycocalyx. This shedding of the glycocalyx is thought to be a mediator of the coagulopathy seen in trauma patients. Clinical studies have demonstrated increases in shed glycocalyx in the blood after trauma, and animal studies have measured glycocalyx disruption in blood vessels in the lung, skeletal muscle, and mesentery. However, no study has measured glycocalyx disruption across a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…15,45 Our previous work has shown that the vasculature in the lung are disproportionately exposed to ROS after ischemia-reperfusion and are most vulnerable to glycocalyx injury. 21 The present study confirmed that DMM protects the glycocalyx in the lung. This protective effect was seen in both large and small vessels, as DMM protected the glycocalyx in the pulmonary artery and the capillary vessels in the alveoli.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…15,45 Our previous work has shown that the vasculature in the lung are disproportionately exposed to ROS after ischemia-reperfusion and are most vulnerable to glycocalyx injury. 21 The present study confirmed that DMM protects the glycocalyx in the lung. This protective effect was seen in both large and small vessels, as DMM protected the glycocalyx in the pulmonary artery and the capillary vessels in the alveoli.…”
Section: Discussionsupporting
confidence: 84%
“…Glycocalyx staining was performed to determine staining intensity of the endothelial glycocalyx as previously described. We performed these experiments because our prior work has shown that the endothelial glycocalyx in lung tissue is preferentially affected in HS 21 . Briefly, flash frozen tissue was sectioned in a cryostat at −20°C at a section thickness of 10 μm, and the sections were affixed to room temperature glass slides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While shedding of the endothelial glycocalyx is thought to affect the systemic vascular endothelium as the glycocalyx is ubiquitous, there may be organ-based differences. Recently Abdullah et al [55] evaluated glycocalyx shedding after hemorrhagic shock in a rat model by staining multiple organs with a syndecan-1 antibody. This demonstrated that the greatest glycocalyx disruption occurred in the vasculature of the lungs and intestine, where the highest levels of endothelial reactive oxygen species were also measured, and shedding to a lesser extent occurred in the brain, heart, and skeletal muscle.…”
Section: The Pathophysiology Of the Endothelial Glycocalyx And Vascul...mentioning
confidence: 99%